Magnitude and severity of anemia, its clinico-pathological types and the burden of iron deficiency in adolescent boys: Is weekly iron supplementation a step in the right direction - Sahu, Monalisha; Das, Ranjan; Nangia, Anita (Indian Journal of Community Health, 2014)
Background: Iron-deficiency anaemia is a major global public health problem affecting all stages of life cycle. Adolescent boys are also vulnerable to it owing to their growth spurt and inadequate dietary intakes. Assessment of anaemia and quantification of the burden of iron-deficiency anemia in them has been less studied. Knowledge of these aspects at the local level may help public health functionaries take appropriate decisions. Objectives: i) To assess the magnitude and severity of anaemia in adolescent boys residing in a peri-urban community of Delhi, ii) To identify the clinico-pathological type of anemia and among adolescent boys residing in a South Delhi locality iii) To estimate the burden of iron deficiency in them. Materials and Methods: A Community-based cross sectional study was conducted in 250 adolescent boys at Mehrauli in South Delhi in 2012. Hemoglobin estimation was done by Hemocue method, severity of anaemia assessed as per WHO criteria. To assess the clinico-pathological type of anaemia peripheral smears were prepared and stained with Wright Giemsa stain for assessing red-cell morphology. Serum ferritin estimation by MAb ELISA was done to confirm Iron deficiency. Statistical analysis: SPSS ver 12 and Epi Info ver 7 softwares were used for data entry and analysis. Mean and SD was calculated for quantitative variables while qualitative variables were compared by percentages. Chi-square test and ANOVA was used for checking statistical significance in observed differences. Results: Pallor was seen in 14.6%. Prevalence of anaemia was 16.4% with proportion of mild, moderate and severe anemia being 66.7%, 31.2% and 2.1% respectively. Mean haemoglobin concentration was 13.03 ±1.18 gm% (min 7.6, max 15.0). Anemia prevalence increased with increase in age (9.6%, 18.4% and 26.0% in early, middle and late adolescence, respectively). Clinico-pathological type of anaemia was microcytic-hypochromic in 50.0%, normocytic-normochromic in 17.5%, megaloblastic in 10.0% and dimorphic in 1.2%. Serum ferritin estimation performed on subjects having smear suggestive of iron deficiency led us to conclude that 16.1% had low serum ferritin levels and iron-deficiency anaemia. Statistically significant association of iron-deficiency anaemia was found with age, nutritional status, passage of worms in stool and lack of in-house toilet. Conclusion: Prevalence of anaemia as well as iron deficiency anaemia is low in adolescent boys and therefore is not a public health problem in this section of society. Providing iron supplements may not be warranted to them as is currently being done. More research is needed to identify the cause of such anaemia.